KORBAN ALIH FUNGSI LAHAN DI KELURAHAN SETIANAGARA, KECAMATAN CIBEUREUM, KOTA TASIKMALAYA, JAWA BARAT - Ivanka Marayandini; Trisna Insan Noor (Universitas Galuh Ciamis, 2020)
Cibeureum District is one of the four sub-districts in the City of Tasikmalaya with the highest reduction in paddy fields area. The study was conducted in Setianagara which is included in the LP2B (Sustainable Food Agricultural Land) area but is still experiencing lang conversion. This study aims to determine the profile of victims of land use change, push and pull factors switching land use, and the condition of the victims before and after land use change. The design in this study used a qualitative descriptive design and research techniques using case studies. The information obtained comes from interviews and observations. Informants in this study are victims of land use change. The results showed that the factors driving the conversion of land originated from self and coercion, while the pull factors came from the buyers of the paddy fields and coercion. The situation of farmers before and after land use change has changed for the worse, more stable, and better.